Army at state-building of the Western Ukrainian People’s Republic: organizational and legal framework - Kravchuk, Mykola (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article is devoted to the research of state-building in the western lands of Ukraine, in particular the statebuilding of the Western Ukrainian People’s Republic (hereinafter – WUPR) in the military sphere. The scientific research highlights the peculiarities of the formation of the Ukrainian Galician Army (hereinafter – UGA) and its main stages. The role and significance of the WUPR Army for its state-building is determined. The basic directions of creation and development of the WUPR troops during the specified period are established. The experience of the operation of the WUPR Army, its positive and negative aspects was analyzed and evaluated. The emphasis is on the organizational and legal foundations of the formation of the UGA accented (organizational structure, legislative framework, legal support of state construction and development of the Armed Forces of the WUPR)